Admissions Variables: Predictors of Physician Assistant Student Success. Issue 3 (September 2018) - Honda, Trenton; Patel-Junankar, Dipu; Baginski, Robert; Scott, Rebecca
Abstract : Purpose: Physician assistant (PA) programs have heterogeneous admissions processes, but limited information is available as to which preadmission variables are associated with the greatest PA program success. We assessed the associations between preadmission criteria and PA program outcomes while accounting for numerous potential confounders and potential cohort effects. Methods: In a sample of 147 students from a single New England PA program, we used random intercept multiple regression models to examine the associations between 2 PA program outcomes—Physician Assistant National Certifying Examination (PANCE) scores and PA program grade point averages (GPAs)—and multiple predictors of interest, including undergraduate GPA; hours of paid, hands-on patient care experience; and undergraduate institution rank. Fully adjusted models additionally controlled for age and educationally or economically disadvantaged background. Results: In fully adjusted models, a 1-unit increase in undergraduate GPA (54.55 ± 20.32, P = .012) and a 10% increase in preadmission clinical experience hours (18.32 ± 8.50, P = .033) were significantly associated with increased PANCE scores. When PA program GPA was examined as an outcome, only undergraduate GPA was significantly associated (0.15 ± 0.05, P = .004). Undergraduate institution rank was not a significant predictor in any model. Conclusions: Undergraduate GPA and preadmission clinical experience hours were significant predictors of student outcomes in this small, retrospective cohort study. Undergraduate institution rank was highly nonsignificant in all models. These findings add to the burgeoning literature on admissions predictors of PA program success.